2014
DOI: 10.14202/vetworld.2014.671-680
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of total intravenous anaesthesia using xylazine or dexmedetomidine with propofol in surgical management of canine patients

Abstract: The aim was to evaluate and compare the clinico-physiological, hemodynamic and hematobiochemical effects in response to different total intravenous anaesthesia techniques using xylazine or dexmedetomidine with propofol in canine patients. Materials and Methods:Under a prospective randomized blinded clinical study, 12 apparently healthy adult dogs (14.27±3.2 kg) divided into two groups (n=6). Animals were administered with xylazine (0.5 mg/kg body weight IV) in X group or, dexmedetomidine (10 μg/kg body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…The increased CORT level is in agreement with the findings of [ 37 ], indicating that CORT concentration could be suppressed 30 min after induction of West African Dwarf goats with xylazine and propofol and a surge in CORT concentrations was observed 2 h postsurgery. Similar findings were reported postsurgery [ 33 , 38 ]. The value of CORT began to fall at 24 h postsurgery for the three groups and was significant at 24 h for Group 3 and 96 h for both Groups 1 and 3.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased CORT level is in agreement with the findings of [ 37 ], indicating that CORT concentration could be suppressed 30 min after induction of West African Dwarf goats with xylazine and propofol and a surge in CORT concentrations was observed 2 h postsurgery. Similar findings were reported postsurgery [ 33 , 38 ]. The value of CORT began to fall at 24 h postsurgery for the three groups and was significant at 24 h for Group 3 and 96 h for both Groups 1 and 3.…”
Section: Discussionsupporting
confidence: 90%
“…Xylazine is an alpha2-adrenoceptor agonist that is used for premedication, sedation, and analgesia in small animal practice [ 32 ]. It has marked anesthetic effect [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was possibly due to pooling of erythrocytes in to spleen due to decreased in sympathetic stimulation or hemodilution. Our results are in accordance with the (Jena et al, 2014). However, the values of white blood cells nonsignificantly increased (P>0.05) in xylazine-propofol receiving group as compared to diazepam-propofol and medetomidine propofol group.…”
Section: Respiratory Rate Depressionsupporting
confidence: 91%
“…As the previous studies explained that medetomidine alone cannot produce prolonged and rapid analgesia (Baker et al, 2011) therefore this might be due to the synergestic effect of medetomidine along with propofol. Medetomidine has increased specificity for the alpha-2 receptor, and increased analgesic potency compared to xylazine (Jena et al, 2014). Medetomidine is preferred over xylazine in dogs (Lemke, 2007).…”
mentioning
confidence: 99%
“…The findings of the present study concurred with Sankar et al (2011) who had also observed a decrease in Hb, PCV, TEC, monocytes, eosinophil and neutrophilia during ketamine or propofol anaesthesia in acepromazine-xylazine premedicated dogs. Other workers are also reported similar results during the continuous infusion of propofol (Jena et al 2014, Ratnesh et al 2014, ketofol (Kumar et al 2014) and ketamine anaesthesia (Venugopal et al 2002) in dogs. The decreasing trend of haematological parameters in the present experiment might be due to the splenic pooling of erythrocytes that occur with most of the other anaesthetics.…”
Section: Haematological Observationsmentioning
confidence: 61%